Effect of blackberry anthocyanins and its combination with tea polyphenols on the oxidative stability of lard and olive oil - Chen, Han; Zhao, Hui-fang; Meng, Xiu-hua; Chen, Jian; Wu, Wen-long; Li, Wei-lin; Lü, Han (Frontiers in Nutrition, 2023)
To investigate the protective effect of blackberry anthocyanins (BA), tea polyphenols (TP) and their binary mixture on the oxidative stability of edible oils during the storage, BA, TP and their binary mixture were added to lard and olive oil. The changes of peroxide value (PV), thiobarbituric acidreactive substances (TBARS), acid value (AV), scavenging capacity of DPPH and ABTS •+ of oil samples were evaluated during accelerated storage. BA were found to have remarkable capability to enhance the antioxidant properties, delay the lipid oxidation and inhibit the deterioration both of lard and olive oil at high temperature process. Furthermore, antioxidant synergistic effect of BA and TP was found both in lard and olive oil for the first time. All these results suggested that BA and its combination mixed with TP might possess the potential value to protect the quality of edible oils.